The role of the neutrophil and formed elements of the blood in an in vitro model of reperfusion injury - John A. Barrett; Claudia K. Derian; Robert S. Swillo; Richard F. Woltmann; Mark H. Perrone (Mediators of Inflammation)
Using The globally ischaemic isolated guinea-pig heart we conducted studies to assess the role of activated neutrophils (PMNs) and the role of the endothelium in reperfusion injury. Reperfusion injury was induced by a 20 min period of global ischaemia followed by a 30 min reperfusion with Krebs' buffer supplemented with f-Met–Leu–Phe (fMLP) and heparinized blood. Ischaemia alone or blood alone resulted in a complete recovery in contractile function measured by developed pressure, fMLP (500 μM) and blood, administered to normoxic hearts did not affect contractile function. The combination of 100 μM fMLP and blood beginning at reperfusion and continuing for 30 min decreased the recovery in contractile function (max. 33 ± 6% reovery) while buffer and 100 pM fMLP resulted in a complete recovery in function. In hearts infused with buffer and neutropenic blood incubated with 100 μM fMLP a complete recovery in function was observed. Isolated peritoneal neutrophils, 7–70 × 105 PMN/ min, incubated with 100 μM fMLP and Krebs' solution decreased contractile function in a concentration-related manner (max. 44 ± 11% recovery). Platelets, plasma or red blood cells alone incubated with fMLP did not decrease recovery in developed pressure. Platelets and PMN incubated with 100 μM fMLP did not, while red blood cells and PMN did, elicit a reduction in recovery in contractile function (34 ± 4% recovery). A 20 min period of global ischaemia destroys the functional integrity of the endothelium (response to Ach). Pre-treatment of the heart with sufficient H2O2 to functionally damage the endothelium, followed by infusion of Krebs' solution supplemented with blood and 100 μM fMLP also elicited a reduction in recovery of contractile function (42 ± 15% recovery). In summary, partially activated neutrophils play a major role in reperfusion injury and there exists a cooperativity between the RBC and PMN in this model.